Molecular Detection and Identification of Brettanomyces/Dekkera bruxellensis and Brettanomyces/Dekkera anomalus in Spoiled Wines - Cocolin, Luca (American Society for Microbiology, 2004)
In this paper we describe the development of a PCR protocol to specifically detect Brettanomyces bruxellensis and B. anomalus. Primers DB90F and DB394R, targeting the D1-D2 loop of the 26S rRNA gene, were able to produce amplicons only when the DNA from these two species were used. No amplification product was obtained when DNA from other Brettanomyces spp. or wine yeasts were used as the templates. The 305-bp product was subjected to restriction enzyme analysis with DdeI to differentiate between B. bruxellensis and B. anomalus, and each species could be identified on the basis of the different restriction profiles. After optimization of the method by using strains from international collections, wine isolates were tested with the method proposed. Total agreement between traditional identification and molecular identification was observed. The protocol developed was also used for direct detection of B. bruxellensis and B. anomalus in wines suspected to be spoiled by Brettanomyces spp. Application of culture-based and molecular methods led us to the conclusion that 8 of 12 samples were spoiled by B. bruxellensis. Results based on the application of molecular methods suggested that two of the eight positive samples had been infected more recently, since specific signals were obtained at both the DNA and RNA levels.